The Effectiveness Of Squeeze Of Sambiloto (Andrographis Paniculata) Leaves On The Mortality Of Larvae Aedes Aegypti - Graffico Eryza Oldiara; Riandini Aisyah; Safari Wahyu Jatmiko; Devi Usdiana Rosyidah; Rochmadina Suci Bestari (Saintika Medika, 2020)
Dengue hemorrhagic fever has become a deadly disease since 2013. Dengue fever is a disease caused by dengue virus transmitted to humans through the bite of the Aedes aegypti. Eradication using chemical larvacides still has many disadvantages so that natural larvacides from plants are needed, one of which is larvacide from the squeeze of the sambiloto (Andrographis paniculata) leaves. The squeeze of the sambiloto leaf (Andrographis paniculata) contains flavonoids, alkaloids, tannins and saponins which have natural larvacidal activity. This research aims to determine the killing power of the squeeze of sambiloto (Andrographis paniculata) leaves against Aedes aegypti larvae and determine the most effective concentration as larvicide. This research was experimental laboratory with post test only controlled group design method. There are 600 instar III Aedes aegypti Larvae randomly divided into 6 groups (5%, 10%, 15%, 20%, aquadest and abate). Using 4 repetitions each group was observed every 6 hours for 24 hours. Based on the results of the Kruskal-Wallis non-parametric statistical test obtained p-value = 0,001 which means there are significant differences in larvicidal effects between groups. The concentration of 15% and 20% are the most effective in killing the larvae of Aedes aegypti.